Parallel Computing Technologies 10th International Conference, PaCT 2009, Novosibirsk, Russia, August 31-September 4, 2009, Proceedings - Malyshkin, Victor (Theoretical Computer Science and General Issues, 2009)
This book constitutes the proceedings of the 10th International Conference on Parallel Computing Technologies, PaCT 2009, held in Novosibirsk, Russia on August 31-September 4, 2009. The 34 full papers presented together with 2 invited papers and 7 poster papers were carefully reviewed and selected from 72 submissions. The papers are organized in topical sections on models of parallel computing, methods and algorithms, fine-grained parallelism, parallel programming tools and support, and applications.